The Influence Of Work Environment and Workload on the Peformance Of Preparation Employees At PT Adis Dimension Footwear Tangerang Regency - Nurohmah, Nurohmah; Yulandari, Sri; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the simultaneous influence of the work environment and workload on the performance of employees in the Preparation department at PT. Adis Dimension Footwear Balaraja-Tangerang.This study used a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all employees in the production department at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 63 respondents. This study used a saturated sampling technique due to the small population size; therefore, the entire population of 63 employees was used as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis with SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, the work environment significantly influences the performance of employees in the Preparation department at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (4.936>2.000) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, workload significantly affects the performance of employees in the Preparation section at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (2.906>2.000) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, the work environment and workload significantly affect the performance of employees in the Preparation section at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated F value> F table (51.641>3.15) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that work environment and workload variables, both partially and simultaneously, significantly influence the performance of employees in the Preparation department at PT. Adis Dimension Footwear Balaraja-Tangerang.